Nilai Penting Makroalga di Muara Pantai Desa Pinotu, Kecamatan Toribulu Kabupaten Parigi Moutong - Kaloso, Aan Febriawan (Jurnal Kreatif Online, 2020)
This study aims to determine the importance of the type of macroalgae in the estuary of Pinotu Village, Toribulu District, Parigi Moutong Regency. The sampling technique used was the line transect method with a modification of the placement of the plot of 1 x 1 m size. Furthermore, it was analyzed using an Important Value Index formula. The results showed that there were 19 types of macroalgae, consisting of Halimeda opuntia 23.74%, Boergesiana forbesii 7.62%, Chaetomorpha javanica 36.02%, Codium decorticatum 3.29%, Dictyosphaeria cavernosa 2.19%, Dictyota bartayresiana 28 , 14%, Hydroclathrus clathratus 0.31%, Padina australis 50.72%, Sargassum sp. 10.15%, Achantophora specifera 2.59%, Achantophora muscoides 24.22%, Amphiroa fragilissima 18.40%, Eucheuma spinosum 5.93%, Galaxaura rugosa 0.31%, Gracilaria edulis 12.89%, Gracilaria salicornia 17 , 61%, Hypnea asperi 49.92%, Hypnea cervicornis 5.38% and Tricleocarpa fragilis 0.56%.